Compulsory vaccinations for children: Balancing the competing human rights at stake. Issue 3 (September 2019) - Camilleri, Francesca
Vaccination for children has been a controversial topic for decades and lately it has regained particular importance. We have seen an increase in vaccine hesitancy and decrease in vaccine confidence throughout Europe, particularly due to vaccine-safety concerns by parents. Consequently, vaccination rates for children have dropped and this in turn has led to an increased spread of vaccine-preventable infectious diseases, such as measles. As a reaction to this phenomenon of vaccine hesitancy, several European countries have introduced, while others are in the process of introducing, laws making vaccinations compulsory for children for a number of vaccine-preventable childhood diseases. The introduction of such laws affects and gives rise to several competing interests of the parents, the child and the State. Against this background, this article seeks to determine how the European Court of Human Rights should balance the competing human rights that are at stake in cases concerning compulsory vaccinations for children.